Postactivation potentiation in endurance-trained male athletes - Hamada, T.; Sale, D. G.; MacDougall, J. D. (Medicine & Science in Sports & Exercise, 2000)
Purpose: The purpose of the study was to determine whether postactivation potentiation (PAP) was enhanced in the trained muscles of male endurance athletes. Methods: Triathletes (TRI), distance runners (RUN), active controls (AC), and sedentary control subjects (SED) (N = 10 per group) performed 10-s maximal isometric contractions (MVC) of the elbow extensor and ankle plantarflexor muscles. Maximal twitch contractions were evoked (percutaneous stimulation) before and during a 5-min period after the MVC. PAP was measured as the percentage change in peak twitch torque post-MVC. Results: TRI, who train both upper and lower limb muscles, had enhanced (relative to SED) PAP in both elbow extensor and plantarflexor muscles. In RUN, who train only the lower limbs, enhanced PAP was restricted to the plantarflexors. AC, whose main activity was upper and lower limb weight training, also had enhanced PAP in both muscle groups, although the enhancement in the plantarflexors was not as great as in TRI and RUN. Conclusion: PAP is enhanced in endurance athletes. Enhanced PAP may counteract fatigue during endurance exercise. The mechanism(s) responsible for the enhanced PAP remain to be determined.